Quantum Metrology for High-Precision Measurement of Fundamental Constants - Tan, Jaden; Tan, Marcus; Chan, Rachel (Journal of Tecnologia Quantica, 2024)
High-precision measurements of fundamental constants have an important role in modern physics and technology. Uncertainty in measurements using classical methods is a major obstacle in improving the accuracy and validation of physical theories. Quantum metrology, which makes use of the phenomenon of quantum entanglement and superposition, offers a solution to overcome these limitations. This study aims to evaluate the effectiveness of quantum metrology in improving the measurement accuracy of fundamental constants, such as Planck’s constant and Newton’s gravity. The research was conducted using an experimental design with quantum sensing-based devices, such as quantum interferometers and ion traps. The data were analyzed to compare the level of measurement uncertainty between classical methods and quantum metrology. Case studies were conducted in a microgravity environment to test the reliability of this technology under extreme conditions. The results showed that quantum metrology significantly reduced measurement uncertainty to two orders of magnitude compared to classical methods. The technology has also proven to be effective in extreme conditions, providing flexibility for applications outside of the laboratory. The conclusion of the study confirms that quantum metrology is able to overcome the limitations of classical methods and has great potential to support the development of global measurement standards in the future.